Value Co-Creation dan Pengaruhnya terhadap Customer Loyalty dalam Ekosistem Digital: Analisis Regresi Sederhana - Raga Aquino; E. Rahmat Taufik; Heri Sapari Kahpi; Suhroji Adha (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This research is motivated by the increasing interaction between customers and various digital platforms, which has given rise to the phenomenon of value co-creation, where customers no longer act as passive users but are actively involved in creating service value. This study aims to examine the effect of Value Co-Creation (X) on Customer Loyalty (Y) in the digital ecosystem in Indonesia. The research method used a quantitative approach with a survey technique, involving respondents who had been active users of digital platforms for at least six months. Data analysis was performed using simple regression in SPSS to examine the direct relationship between variables. The results show that Value Co-Creation has a positive and significant effect on Customer Loyalty, meaning that the higher the customer's involvement in the co-creation process, the higher their level of loyalty to the digital platform. Theoretically, this finding strengthens the literature on the importance of customer participation in digital services as a factor in shaping loyalty. Practically, this research provides implications for digital platform managers to continue encouraging user participation through interaction, feedback, and personalization to increase customer retention and loyalty.